"Optimizing the operational effiency of the Faculty Business and Management Integrated System (FBMIS)". - UiTM, Faculty of Business and Management (UiTM, 2024)
Grant from the Internal Funding of the Faculty Business and Management, totaling RM26,100.00 for a project titled "Optimizing the operational effiency of the Faculty Business and Management integrated system (FBMIS)".